The hilly-gully watershed exhibits distinct deep soil moisture characteristics: a comparative study of paired watersheds in the Chinese Loess Plateau - Zhu, Hongsheng; Wang, Zihan; Zhao, Jiongchang; Lin, Jiaming; Qian, Shuo; Wang, Liping; Yu, Yang; Cavalli, Marco (Frontiers in Plant Science, 2025)
Deep soil moisture constitutes a critical component of hydrological processes in the Loess Plateau, playing an essential role in sustaining vegetation growth, maintaining ecosystem stability, and serving as an important indicator of regional water resource carrying capacity. However, the mechanisms by which long-term vegetation restoration influences deep soil moisture remain insufficiently understood. In this study, we selected two typical paired small watersheds–an Artificial forest watershed and a Farmland watershed-located in the Caijiachuan watershed in the hilly-gully region of the Loess Plateau in western Shanxi Province, China. Based on in situ measurements of soil moisture (0–500 cm) during the 2024 growing season (May-October), the vertical distribution and spatial variability of soil moisture have been systematically analyzed, and the impacts of long-term vegetation restoration on deep soil moisture content have been assessed. The results revealed significant differences between the paired watersheds. The average soil moisture content in the Farmland watershed (0.096 g/g) was significantly higher than in the Artificial forest watershed (0.070 g/g), indicating that artificially introduced vegetation has substantially reduced deep soil moisture reserves. Land use has pronouncedly influenced deep soil moisture, with farmland and native grassland exhibiting the highest moisture retention capacity, while vegetation restoration sites showed the lowest levels. Deep-rooted plantations in the Artificial forest watershed markedly intensified soil moisture deficits in the 200–500 cm layers, whereas the Farmland watershed exhibited comparatively moderate deficits. Moreover, soil moisture spatial heterogeneity was significantly greater in the Farmland watershed, while long-term vegetation restoration promoted a more homogeneous distribution of deep soil moisture. Overall, large-scale restoration dominated by deep-rooted species exerted substantial impacts on deep soil moisture dynamics. These findings provide a scientific basis for vegetation restoration planning and watershed management in the Loess Plateau region.